The conceptualisation of civic energy cooperatives as change agents in the German energy transition - Insa Thimm (Spatial transformation: Processes, strategies, research design, 2022)
Civic energy cooperatives play an essential role in shaping the transformation of the German energy system. They contribute significantly to the decentralised expansion of renewable energy and to the acceptance of the energy transition. This paper aims to shed light on the role of civic energy cooperatives as change agents in the energy transition. A civic engagement approach was chosen because in addition to their economic orientation, civic energy cooperatives are known for their social component with a focus on the common good. The paper will demonstrate the civil society potential of civic energy cooperatives, despite their economic activity and profit motives. The paper will also present the concept of change agents from transformation research and demonstrate the value of the concept for situating civic energy cooperatives within the social context of the energy transition.
urn:nbn:de:0156-08911597; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Energy transition; civic energy cooperatives; civic engagement; change agents